Perceived barriers to medication adherence remain stable following solid organ transplantation - Danziger-Isakov, Lara (Pediatr Transplant, 2019)
Perceived barriers to adherence have previously been investigated in solid organ transplantation (SOT) to identify plausible intervention targets to improve adherence and transplant outcomes. . Fifteen centers in Clinical Trials in Organ Transplantation in Children enrolled patients longitudinally. Patients >8 years completed Adolescent Scale(AMBS) at two visits at least 6 months apart in the first 17 months post-transplant while their guardians completed Parent Medication Barriers Scale (PMBS). Differences over time for pre-identified AMBS/PMBS factors were analyzed. Perceived barrier reporting impact on subsequent tacrolimus (TAC) levels was assessed. 123 patients or their guardians completed PMBS or AMBS. 26 were 6–11 years; 97 were >12. The final cohort consisted of kidney (66%), lung (19%), liver (8%), and heart (7%) recipients. Unadjusted analysis showed no statistically significant change in reported barriers from visit 1 (median 2.6 months, range 1.2–3.7 post-transplant) to visit 2 (median 12, range 8.9–16.5). Of 102 patients with TAC levels, 74 had a single level reported at both visits. The factor of ‘Disease frustration’ was identified through the PMBS/AMBS questions about fatigue around medication and disease. Each point increase in ‘disease frustration’ at visit 1 on the AMBS/PMBS doubled the odds of a lower-than-threshold tacrolimus level at visit 2. No clear change in overall level of perceived barriers to medication adherence in the first-year post-transplant were seen in pediatric SOT. However, disease frustration early post-transplant was associated with a single subtherapeutic TAC levels at 12 months. A brief screening measure may allow for early self-identification of risk.